2013
DOI: 10.1007/s00296-013-2797-x
|View full text |Cite
|
Sign up to set email alerts
|

Undifferentiated spondyloarthritis in a heterogeneous Brazilian population: an eight-year follow-up study

Abstract: The aim of the present study was to describe the outcomes of Brazilian patients with undifferentiated spondyloarthritis during an eight-year follow-up period. Patients fulfilling the European Spondyloarthritis (SpA) Study Group Classification Criteria were enrolled. Forty patients were seen at baseline, and 36 participated in the follow-up study. Twenty-three (58%) were female, and there were 24 (60%) African Brazilians enrolled. HLA-B27 was positive in 18 (45%) patients. At disease onset, the first presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The summaries of 16 eligible studies were shown in Table 1 and all studies were prospective. Of the 16 studies included in present study, 3 from Latin America (2 from Brazil [ 16 , 28 ] and 1 from Mexico [ 27 ] ), 3 from Europe (1 from Spain [ 17 ] and 2 form Germany [ 15 , 30 ] ), and 10 from Asia (1 from India [ 29 ] and 9 from China [ 14 , 31 – 38 ] ). The total number of patients with uSpA participated in follow-up was 2134, with sample sizes ranged from 35 to 648.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The summaries of 16 eligible studies were shown in Table 1 and all studies were prospective. Of the 16 studies included in present study, 3 from Latin America (2 from Brazil [ 16 , 28 ] and 1 from Mexico [ 27 ] ), 3 from Europe (1 from Spain [ 17 ] and 2 form Germany [ 15 , 30 ] ), and 10 from Asia (1 from India [ 29 ] and 9 from China [ 14 , 31 – 38 ] ). The total number of patients with uSpA participated in follow-up was 2134, with sample sizes ranged from 35 to 648.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] The progression rate of 8 years was robust because of the low heterogeneity. Irrespective of the discrepancy of the number of subjects between the 2 studies, [ 28 , 32 ] the enrollment of study subjects in these 2 studies was almost synchronous, which may improve the rationality of data merging. Higher heterogeneity was detected in the rate of 10 years, and it maybe accounts for the 3 studies [ 14 – 16 ] which come from different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Jinnan 1 , X. Dan 1 , G. Chong 2 , L. Xiaofeng 1 . 1 The Second hospital of Shanxi Medical University, Taiyuan, China; 2 Brigham and Women's Hospital, Boston, USA Background: The association of undifferentiated spondyloarthritis (uSpA) with the imbalance of Th17/Treg cells is still unclear. By inhibiting mTOR, rapamycin promotes the proliferation of Treg cells and inhibits the growth of Th17 cells.…”
Section: Rapamycin Restores the Balance Between Th17 And Regulatory Tmentioning
confidence: 99%